Functional Properties of Heat-Moisture-Treated Arrowroot (Maranta arundinacea L.) Flour for Instant Porridge Application - Livia Tadius, Melissa; Arum Anugrahati, Nuri; J.N Parhusip, Adolf (Reaktor, 2025)
Instant porridge, usually made from high glycemic index rice flour, can be substituted with arrowroot flour, which has a lower glycemic index. Heat moisture treatment (HMT) can enhance the water absorption capacity of arrowroot flour. The research aims to determine the effect of HMT temperature and time on the physicochemical characteristics and functional properties of arrowroot flour, to identify the optimal HMT conditions based on water absorption capacity, and to determine the physicochemical characteristics and functional properties of instant arrowroot porridge with the selected HMT treatment.   The HMT method was conducted at temperatures of 100°C, 110°C, and 120°C for 30 minutes, 60 minutes, and 90 minutes. The experimental design is a Completely Randomized Design (CRD) with two factors arranged in a 3 × 3 factorial scheme, with three replications per treatment. The preliminary stage involves the production of arrowroot flour, the primary research phase I involves the modification of arrowroot flour using HMT, and the primary research phase II involves the production of instant arrowroot porridge. The experiment was limited to a laboratory scale due to equipment capacity, especially the oven used for HMT, which restricted batch size and may affect scalability. The results showed that HMT can increase yield, water absorption capacity, total dietary fiber content, and resistant starch content, while decreasing moisture content, total carbohydrate content, and glycemic carbohydrate. The selected HMT arrowroot flour treatment was at 110°C for 60 minutes with the highest water absorption capacity (2.11 g/g). The characteristics of instant arrowroot porridge include 11.03% moisture content, 2.32 g/g water absorption capacity, 2.69 ml/g rehydration capacity, 25.89 seconds/g rehydration time, 70.70% total carbohydrate content, 6.60% dietary fiber content, 64.10% glycemic carbohydrate, and 5.62% resistant starch content. This study shows that HMT-modified arrowroot flour could be a healthier alternative to rice flour in food products, offering a lower glycemic index. The improved functional properties, such as higher water absorption and more dietary fiber, make it suitable for products like instant porridge, which can help people manage blood sugar levels.